Sexual Abuse of Girls in Post-Revolutionary Mexico: Between Legitimation and Punishment. Issue 1 (1st March 2021) - Sosenski, Susana
Abstract: In this article, I analyze certain ideas circulating in early twentieth-century Mexico about the sexual abuse of young and adolescent girls, and how ideas about the prohibited, permitted, or legitimate uses of their bodies were sustained by complex webs of corruption and injustice. Not only criminals but also families, lawyers, judges, and police officers commonly considered the bodies of young girls from working-class families as legitimate spaces of sexual violence. Some newspapers also propagated this idea. Prevailing notions about the gender and sexuality of young and adolescent girls fed into family-based concepts of honor and chastity that were reproduced in practices and narratives related to the abuse of children's bodies, and this contributed to the perpetuation of a rape culture among Mexicans.